ANALYSIS OF OXIDATIVE STRESS MARKERS MALONDIALDEHYDE, GLUTATHIONE, NITRIC OXIDE, AND PRORENIN LEVEL IN PREECLAMPSIA PLACENTAL TISSUES - Prijanti, Ani Retno; Marissa, Nelly; Paramita, Reni; Humaira, Sarah; Nabila, Eldesta Nisa; Wijaya, Anthony Eka; Fadila, Asiyah Nurul; Purwosunu, Yuditiya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Preeclampsia was a syndrome of hypertension proteinuria in pregnant women. In failure of pseudo vasculogenesis, there is persistency of endothelial and smooth muscle cell of vessel wall in spiral artery. Spiral artery could not be emphasis and lead to relative hypoxia, and oxidative stress in placental tissues. Endothelial cell has property to produce nitric oxide (NO) that can dilated vessel. Placenta also produces prorenin, to maintain vascular wall tonicity. Therefore, we want to uncover the property of placenta is there any capacity of prorenin, is that prorenin could overcome the NO level, or is there any depression of NO production, and any oxidative stress. Methods: This observational study was used caseâ€“control design. We search preeclampsia cases during September-December 2015. We used preeclampsia placentas from early and late onset. We collect preeclampsia placentas from Cipto Mangunkusumo and normal placentas from Budi Kemuliaan Hospital. We used 30 preeclampsia placentas and 30 normal placentas. Markers measured were NO and prorenin. NO was measured using colorimetric assay kit (K262-200/ BioVision), and prorenin was measured using human prorenin enzyme-linked immunosorbent assay kit (ab157525/ Abcam). Glutathione (GSH) was measured using Ellman method and malondialdehyde (MDA) using Wills method. Results: Prorenin concentration between normal and preeclampsia placenta was analyzed using Mannâ€“Whitney and show that there had no significant difference between preeclampsia and normal placentas (p=0.23). Besides, NO data analyzed using independent t-test show significant differences between preeclampsia and normal placentas (p=0.001). The difference between normal and preeclampsia GSH concentration was not significant (p=0.757), besides the difference between normal and preeclampsia MDA concentration was significant (p=0.000). Conclusion: NO concentration in preeclampsia placenta was increase, higher than normal placenta. There was no effect of preeclampsia on prorenin concentration and GSH. There was marked decrease of MDA in preeclampsia placentas.